THE TYPE OF STUDENTS’ MOTIVATION IN ONLINE ENGLISH LEARNING - I Gusti Agung Vony Purnama; I Gusti Agung Vony Purnama (Universitas Lambung Mangkurat, 2022)
Nowadays, during the pandemic of covid-19, the learning process in higher education is conducted through online learning particularly for English subject and this is a new thing both for the lecturer and students as well. This situation can affect the students’ motivation in learning particularly English as a foreign language. Based on this phenomenon, the objectives of this study was to find out the students’ motivation type in learning English in Institute of Business STIKOM Bali. The subject of this study was the students who learn English in the first semester academic year 2020/2021. The result of this study revealed that the students’ type motivation in learning English was a type of an integrative motivation rather than instrumental motivation. However, based on the mean score of both motivations, it was also on the high level of motivation. It is hoped that this finding can be used as a reference to conduct an advance research in the same area.